2005
DOI: 10.1161/01.atv.0000177805.65864.d4
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-Activated Receptor γ Ligands Stimulate Endothelial Nitric Oxide Production Through Distinct Peroxisome Proliferator-Activated Receptor γ–Dependent Mechanisms

Abstract: Objective-We recently reported that the peroxisome proliferator-activated receptor ␥ (PPAR␥) ligands 15-deoxy-⌬ 12,14 -prostaglandin J 2 (15d-PGJ 2 ) and ciglitazone increased cultured endothelial cell nitric oxide (NO) release without increasing the expression of endothelial nitric oxide synthase (eNOS). The current study was designed to characterize further the molecular mechanisms underlying PPAR␥-ligand-stimulated increases in endothelial cell NO production. Methods and Results-Treating human umbilical vei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
113
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(123 citation statements)
references
References 66 publications
10
113
0
Order By: Relevance
“…In the present study, eNOS expression was unaffected by nifedipine in the SHRSP heart with or without GW9662. It has also been reported that PPAR agonists stimulate NO release through a mechanism related to NO production 42) but unrelated to eNOS expression 43) , and decrease NAD(P)H oxidase-dependent ·O2 production 41) . Although in the present study, circulating concentrations of NO metabolites were not measured, they may follow a similar pattern to the relaxant responses in SHRSP groups.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, eNOS expression was unaffected by nifedipine in the SHRSP heart with or without GW9662. It has also been reported that PPAR agonists stimulate NO release through a mechanism related to NO production 42) but unrelated to eNOS expression 43) , and decrease NAD(P)H oxidase-dependent ·O2 production 41) . Although in the present study, circulating concentrations of NO metabolites were not measured, they may follow a similar pattern to the relaxant responses in SHRSP groups.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have shown that AA and PPARs stimulate NO production in many tissues and cells (7,13,15,19,21,22). AA has been reported to stimulate cGMP accumulation via NO production in vascular smooth muscle cells (9).…”
Section: Effects Of Bay-60-7550 (A Pde2 Inhibitor) On Ca 2ϩ -Regulatementioning
confidence: 99%
“…This effect appears to be independent of its AT 1 R blocking actions. 19 PPAR␥ signaling has important antiatherogenic properties 20 and is associated with decreased oxidative stress 21 and increased NO formation, 22 which are 2 of the most important component affecting the process of aging in ECs. [2][3][4][5]11,12 On the basis of these observations, we examined the effect of telmisartan on oxidative stress as well as ADMA-NO pathway through AT 1 R or PPAR␥ signaling during aging of ECs.…”
mentioning
confidence: 99%